Dampak Shock Impulse Response dari Investasi, Indeks Pembangunan Manusia (IPM), dan Upah Minimum terhadap Pertumbuhan Ekonomi Kalimantan Barat selama Pandemi COVID-19 - Riska Ayulia; Luqman Luqman; Sumin (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2025)
This study aims to comprehensively examine the long-term and short-term effects of foreign direct investment, domestic investment, Human Development Index (HDI), and minimum wage on economic growth in West Kalimantan over the 1996–2023 period, with a primary focus on the COVID-19 pandemic era. The pandemic has severely impacted regional economic stability, and West Kalimantan, a resource-based province, has experienced significant shocks. A quantitative approach was applied using time series analysis with Vector Autoregression (VAR), Granger Causality Test, Johansen Cointegration Test, and Impulse Response Function (IRF). Secondary data were obtained from the Central Statistics Agency (BPS), the Investment Coordinating Board (BKPM), and other governmental sources. The findings indicate that all variables significantly affect economic growth in both the short and long term. Domestic investment and HDI contribute positively and consistently, while foreign investment exhibits high volatility. Minimum wage has a negative impact in the short term but turns positive in the medium term. The study provides strategic policy recommendations to strengthen the regional economic foundation through human capital development, domestic investment enhancement, and productivity-based wage policies. The implications are relevant for post-pandemic policy formulation and enhancing regional economic resilience against future crises.